2020
DOI: 10.1021/acs.jpca.0c03646
|View full text |Cite
|
Sign up to set email alerts
|

Electronic States and Nonradiative Decay of Cold Gas-Phase Cinnamic Acid Derivatives Studied by Laser Spectroscopy with a Laser-Ablation Technique

Abstract: We performed UV spectroscopy for p-coumaric acid (pCA), ferulic acid (FA), and caffeic acid (CafA) under jet-cooled gas-phase conditions by using a laser-ablation source. These molecules showed the S1(1ππ*)–S0 absorption in the 31 500–33 500 cm–1 region. Both pCA and FA exhibited sharp vibronic bands, while CafA showed only a broad feature. The decay time profile of the 1ππ* state was measured by picosecond pump–probe spectroscopy, and the transient state produced through the nonradiative decay (NRD) from 1ππ*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
4
11
0
Order By: Relevance
“…Since the ionisation energy of the lower-lying electronically excited states is higher than from the initially excited state, they will be more efficiently ionised when ionisation takes place with 193 nm instead of ∼ 320 nm. Such a situation is quite similar to what has been observed for cinnamates and coumarates for which it was concluded that after excitation of the bright 1 ππ* state internal conversion to a dark 1 nπ * state and intersystem crossing to the triplet manifold occurred [15,26,30,33,37,46]. We thus conclude that internal conversion pathways to other electronically excited states also play a significant role for MS.…”
Section: Methyl Sinapatesupporting
confidence: 87%
“…Since the ionisation energy of the lower-lying electronically excited states is higher than from the initially excited state, they will be more efficiently ionised when ionisation takes place with 193 nm instead of ∼ 320 nm. Such a situation is quite similar to what has been observed for cinnamates and coumarates for which it was concluded that after excitation of the bright 1 ππ* state internal conversion to a dark 1 nπ * state and intersystem crossing to the triplet manifold occurred [15,26,30,33,37,46]. We thus conclude that internal conversion pathways to other electronically excited states also play a significant role for MS.…”
Section: Methyl Sinapatesupporting
confidence: 87%
“…Our calculations find that MS adopts a perpendicular geometry of the vinyl double bond in its lowest excited triplet state 57 -similar to the other cinnamates and hydroxycinnamates that have been studied so far 23,43,46,49,70,73 -and predicts that this state has an adiabatic excitation energy of 2.47 eV at the M05-2X/6-31+G(d) level. This would imply an adiabatic ionization energy of T 1 of about 4.95 eV.…”
Section: A Zeke View On the S 1 Excited-state Dynamics Of Mssupporting
confidence: 65%
“…Compared with methyl-4-hydroxycinnamate for which an ionization threshold of 65 154 cm À1 (8.078 eV) has been determined, 18 this implies that the substitution with the two methoxy groups ortho to the hydroxyl group lowers the ionization potential by more than 0.6 eV. For p-coumaric acid and ferulic acid ionization thresholds have been determined of 65 200 and 63 560 cm À1 (8.084 and 7.892 eV), 70 respectively. These thresholds suggest that substitution with one methoxy group leads to a lowering of the ionization potential by 1640 cm À1 (0.203 eV).…”
Section: A Zeke View On the Spectroscopic Properties Of The S 1 And D 0 States Of Ms Conformersmentioning
confidence: 99%
“…It therefore stands to reason that they can be used as starting models for unravelling the NRD dynamics of p-HMC. Upon photoexcitation of p-CA to the 1 ππ* state in the gas-phase, the NRD process shown in Figure 2a dominates, with the observed lifetime of the 1 ππ* and 3 ππ* states measured as ≤10 picoseconds (ps) and 20 ± 4 nanoseconds (ns), respectively [5]. For MC, the same NRD process dominates with the 1 ππ*, 1 nπ* and 3 ππ* states having been experimentally observed.…”
Section: Introductionsupporting
confidence: 57%
“…Cinnamates and coumaric acids have been widely studied to elucidate their remarkable light absorbing properties, driven by efficient non-radiative decay (NRD) pathways [1][2][3][4][5]. In nature, these chromophores are embedded in proteins to enable vitally important processes to occur.…”
Section: Introductionmentioning
confidence: 99%